Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Komik Digital Terhadap Kemampuan Berpikir Kritis Siswa Pada Materi Fotosintesis Kelas IV SD Negeri - Rinda Ayu Mustika Dewi; Desi Nuzul Agnafia; Ririn Setyowati (LP. Ma'arif Janggan Magetan, 2024)
This study aims to identify the impact of implementing the PBL (Problem Based Learning) learning model assisted by digital comic media on students' critical thinking skills in class IV photosynthesis material at State Elementary Schools. The method used is a pre-experimental quantitative approach with one group pretest-posttest as the design. all fourth grade students at SDN Banyuurip, totaling 20 students, were used as the population in this study. The sampling technique used was saturated sampling, involving all 20 students. Data was collected through tests in the form of essay questions. Data analysis includes several tests, including testing the test instrument to ensure the validity and reliability of the questions. The normality test uses the one-sample Shapiro-Wilk test formula, with the data declared to be normally distributed at a significance level of 5% (0.05). The prerequisite test involves a homogeneity test to check the similarity of variance between the two groups, and the hypothesis is tested using a paired sample t-test. . The results of the study show that there is a significant impact of using the PBL learning model with digital comic media on the critical thinking abilities of fourth grade students at state elementary schools in photosynthesis material. This was proven by the results of the paired sample t-test which showed a sig value. (2-tailed) is worth 0.000, therefore H0 is rejected while Ha is accepted.